INTRAHEPATIC PORTAL VEIN ANEURYSM – ULTRASONOGRAPHIC DIAGNOSIS: INTRAHEPATIC PORTAL VEIN ANEURYSM - Duarte , Márcio Luís (2023)
Introduction: Portal venous system aneurysms represent 3% of all venous aneurysms. The most common sites at which portal venous system aneurysms develop are the main portal vein and the confluence of the splenic and the superior mesenteric veins, followed by hepatic hilus. Objective: Report a case and review the literature about this uncommon aneurysm. Case report: A 76-year-old woman with mental confusion and difficulty walking for one hour which abdominal ultrasound detected an increase in the caliber of the portal vein in the hepatic hilum with important collateral vascularization and intrahepatic portal vein aneurysm splenomegaly with the splenic vein of increased caliber, characterizing portal hypertension. Conclusion: Intrahepatic portal vein aneurysm is an uncommon lesion diagnosed by bedside ultrasonography without the need to transfer the patient for computed tomography.